2021
DOI: 10.3390/su13084228
|View full text |Cite
|
Sign up to set email alerts
|

Specific Domains of Creativity and Their Relationship with Intelligence: A Study in Primary Education

Abstract: This study focuses on the relationships between creativity and intelligence. The main objectives of this study are to know the relationship between creativity and intelligence manifested in individuals aged 9 to 12 and to predict the creativity scores from IQ scores. The design of this study is non-experimental with a correlational, cross-sectional, quantitative approach. In order to achieve the stated objectives, several education centres located in Murcia were selected, in which 323 students took part in a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Sala and Gobet (2020), for example, concluded that researchers' optimism about the benefits of music training is unwarranted and possibly stems from a misinterpretation of empirical data. In addition, the idea of the positive influence of creativity (which is inherent to music according to Serrano, 2009) in the teaching-learning process, as well as its subsequent impact on the academic performance of students, seems to have already been confirmed (Alonso et al, 2015;Bernabeu and De la Peña, 2021;López-Martínez and Lorca, 2021;Manetti et al, 2022). On the other hand, Martín López and León del Barco (2009) showed that there are positive correlations between the music grade and the understanding of emotional states, on the one hand, and, on the other, that students with low musical performance, that is, those who failed in music, also obtained the lowest scores in the expression, understanding and regulation of their emotions.…”
Section: Discussionmentioning
confidence: 99%
“…Sala and Gobet (2020), for example, concluded that researchers' optimism about the benefits of music training is unwarranted and possibly stems from a misinterpretation of empirical data. In addition, the idea of the positive influence of creativity (which is inherent to music according to Serrano, 2009) in the teaching-learning process, as well as its subsequent impact on the academic performance of students, seems to have already been confirmed (Alonso et al, 2015;Bernabeu and De la Peña, 2021;López-Martínez and Lorca, 2021;Manetti et al, 2022). On the other hand, Martín López and León del Barco (2009) showed that there are positive correlations between the music grade and the understanding of emotional states, on the one hand, and, on the other, that students with low musical performance, that is, those who failed in music, also obtained the lowest scores in the expression, understanding and regulation of their emotions.…”
Section: Discussionmentioning
confidence: 99%